Time of Postoperative Discharge Following Inpatient Tonsillectomy: A Comparison of Two Techniques - Stephanie M Tominaga; Rodrigo C Silva; Carolyn Ojano-Dirain; William O Collins (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2018)
There are many types of surgical instrumentation and techniques used to perform adenotonsillectomy. The choice of instrument depends on several factors and the benefits of clinical outcomes must outweigh the costs of newer technologies. Our study seeks to compare the discharge times following inpatient adenotonsillectomy using monopolar electrosurgery vs. radiofrequency ablation. Participants included thirty children aged 2 to 8 years old who underwent adenotonsillectomy via monopolar electrocautery or radiofrequency ablation and were admitted for inpatient observation. Eighteen patients underwent tonsillectomy with monopolar electrocautery and 10 patients underwent tonsillectomy with radiofrequency ablation. There was no intergroup difference in age, sex, weight, and indication for tonsillectomy. Total hospital length of stay and variance to a goal of discharge before 8 AM on postoperative day #1 was measured. Results demonstrated statistically significant difference in mean length of stay (19.6 vs. 22.4 hours, p = 0.037) and variance to discharge time (139.5 vs. 15.6 min, p = 0.032) in favor of the radiofrequency ablation group. In this small number of patients, there was significantly earlier discharge times in children undergoing adenotonsillectomy with radiofrequency ablation when compared to monopolar electrocautery. Further cost analysis in a larger sample could determine potential cost benefits to the institution.